2005
DOI: 10.1007/s10661-005-7062-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of bacterial resistance in clinical, food, water and some environmental samples in Southwest Nigeria

Abstract: The resistance pattern and mechanisms of bacterial isolates obtained from clinical origin, soil, industrial effluent, orange juice products and drinking water were studied using commonly used antibiotics. The microbial load of the water samples, industrial effluent and orange juice products were 1.0 x 10(1)-2.25 x 10(6), 2.15 x 10(5), and 3.5 x 10(4)-2.15 x 10(5) cfu mL(-1), respectively. The faecal coliform test revealed that only two out of twenty orange juice products had MPN of 2 and 20, the MPN of water r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
3
21
1
Order By: Relevance
“…There is considerable potential for dissemination of antimicrobial-resistant organisms and resistant determinants from such sources through contamination of food and water (5,11). The risk may be greatest when contaminated wastewater is discharged directly into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable potential for dissemination of antimicrobial-resistant organisms and resistant determinants from such sources through contamination of food and water (5,11). The risk may be greatest when contaminated wastewater is discharged directly into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…A limited group of studies have also shown that antibiotic production mutants are less fit than their antibiotic-producing brethren (25). In situ antibiotic resistance studies have similarly focused on demonstrating the presence of cultivatable antibiotic-resistant bacteria from a number of habitats (20). The significance of this study is that the presence of antibiotic resistance genes (and likely function) is shown to confer an ecological advantage on these microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the production of β-lactamase enzyme by all the isolated organisms was tested on starch agar plates as reported in Lateef et al (2005). Production of β-lactamase is indicated by a clear colorless zone around the colonies when the starch agar plates are flooded with iodine.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%